ALGORITHM OF PREOPERATIVE PREPARATION OF PATIENTS FOR UPPER JAW DEFECT REPAIR IN CONGENITAL CLEFT LIP AND PALATE - Tozhiev F.I.; Azimov A.M.; Muqimov I.I.; Musayev Sh. Sh.; Ismoilhuzhaeva K.G. (Academia Science Repository, 2023)
Congenital cleft lip and palate (CHL) being one of the most frequent malformations of the maxillofacial region since the birth of the child is accompanied not only by the cosmetic defect but also by severe functional disturbances. The high frequency of congenital cleft lip and palate, severe anatomical and functional disorders, the difficulty of social adaptation of such children indicate the particular relevance of this problem. According to the World Health Organization (2009), among all congenital malformations congenital cleft lip and palate takes 2-3rd place, and by the severity of anatomical and functional disorders - the leading place.